The Impact of a Sport-Based Service Learning Course on Participants’ Attitudes, Intentions and Actions Toward Social Change - Fuller, Rhema D.; Evanovich, Justin M.; Bruening, Jennifer E.; Peachey, Jon Welty; Coble, Cassandra J.; Percy, Vernon E.; Maladouangdock, Jesse; Corral, Michael (Journal of Intercollegiate Sport, 2015)
Framed in the context of a sport-based service learning program that engages in interdepartmental university partnerships (including athletics), the current study focused on addressing the need to analyze the long-term impacts of service learning on students’ intentions and actions toward social change. Service learning courses have been shown to facilitate positive outcomes such as increased cultural competency and future intentions toward civic engagement (Bruening et al., 2010, 2014). Building on this knowledge, the current study used in-depth interviews to investigate the social justice-related attitudes, intentions, and behaviors of alumni of a college service learning through sport course. Individual interviews (n = 22) with participants who had completed at least one semester in the course indicated that the course was influential in developing their ability to recognize social inequities. Furthermore, participants indicated future intentions and current involvement in initiatives that address social inequities in their given areas of life. Theoretical and managerial implications for effective academic and intercollegiate athletic partnerships, helping to increase impactful civic engagement and learning opportunities for student-athletes and non-student-athletes, are provided.